2016
DOI: 10.1021/acs.energyfuels.6b01116
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dispersion Stability on Electrorheology of Water-Based ZnO Nanofluids

Abstract: Untreated nanoparticles possess huge surface areas compared to their mass, resulting in strong inter-particle interactions in saline water. This induces a strong tendency of particles' agglomeration, rapid sedimentation and consequently reduced the mobility of nanoparticles in the aquatic environment, which ultimately lowering the effective viscosity of the nano system. This study aimed to investigate the effect of stabilizers on the stability of dielectric nanofluid, to provide a better electrorheological cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…It can be seen that the nanofluid with a ZnO:palmPAS ratio of 1:9 has good stability, because the surfactant added into the nanofluid has not yet reached its saturation point. A previous study documented that the addition of excessive free-surfactant led to lower nanofluidic stability (Adil et al, 2016). The effect of the calcination of the nanoparticles on nanofluidic stability is illustrated in Figure 5.…”
Section: Nanofluid Stability Evaluationmentioning
confidence: 90%
See 1 more Smart Citation
“…It can be seen that the nanofluid with a ZnO:palmPAS ratio of 1:9 has good stability, because the surfactant added into the nanofluid has not yet reached its saturation point. A previous study documented that the addition of excessive free-surfactant led to lower nanofluidic stability (Adil et al, 2016). The effect of the calcination of the nanoparticles on nanofluidic stability is illustrated in Figure 5.…”
Section: Nanofluid Stability Evaluationmentioning
confidence: 90%
“…In the same report, it was also suggested that adding SDS improves stability around alkaline pH. Brine was used in another study with the addition of sodium dodecyl sulfate, sodium dodecylbenzenesulfonate and oleic acid at pH 2, and it was revealed that all the surfactants were able to improve the stability of the nanoparticles (Adil et al, 2016).…”
Section: Synthesis Of Zno Nanoparticles and Their Nanofluid Stabilitymentioning
confidence: 93%
“…14 Several methods have been utilized to prevent such aggregation and produce stable ZnO nanoparticles, including covering ZnO nanoparticles by organic molecules [15][16][17] or inorganic SiO 2 shells 18 and coating 19 the nanoparticle surface by polymerization. Alternatively, other efforts have been undertaken to improve the dispersion stability of ZnO in an organic solvent or in the aqueous phase by using a surfactant, 20 polymer 8,21,22 phosphate, 23 inositol hexakisphosphate, 24 organic matter, [25][26][27] or oleic acid, 6,28 a combination of a polymer and exfoliating agent such as zirconium phosphate; 29 ionic materials; 30 and the controlled combined effect 31 of pH and ionic strength. However, surface modication has a signicant impact on various properties; 4,5 further, it is useful to obtain a stable ZnO solution that allows the dispersion of ZnO nanoparticles in organic and water 7 solvents.…”
mentioning
confidence: 99%
“…However, Ogolo et al [12] found that ZnO dispersed in brine and water caused permeability reduction due to the agglomeration of ZnO NPs into larger particles, which blocked the pore throats of the core. Since stability is one of the key factors for a successful EOR application, Adil et al [135] performed further studies on the stability of ZnO NPs dispersed in water by using different anionic surfactants as stabilizers with various NPs concentrations. They found that 0.1 wt % ZnO NPs stabilized with 0.025 wt % sodium dodecyl benzenesulfonate (SDBS) have the highest stability at 95 • C with viscosity enhancement up to 11%.…”
Section: Zinc Oxidementioning
confidence: 99%